O-ring aortic banding versus traditional transverse aortic constriction for modeling pressure overload-induced cardiac hypertrophy - Schmiedel, Nesrin; Remes, Anca; Valadan, Mohsen; Hille, Susanne; Matzen, Andrea; Frank, Derk; Frey, Norbert; Lehmann, Lorenz; Müller, Oliver J. (JoVE. Video journal, 2022)
Aortic banding in mice is one of the most commonly used experimental models for cardiac pressure overload-induced cardiac hypertrophy and the induction of heart failure. The previously used technique is based on a threaded suture around the aortic arch tied over a blunted 27 G needle to create stenosis. This method depends on the surgeon manually tightening the thread and, thus, leads to high variance in the diameter size. A newly refined method described by Melleby et al. promises less variance and more reproducibility after surgery. The new technique, o-ring- aortic banding (ORAB), uses a non-slip rubber ring instead of a suture with a thread, resulting in reduced variation in pressure overload and reproducible phenotypes of cardiac hypertrophy. During surgery, the o-ring is placed between the brachiocephalic and left carotid arteries. Successful constriction is confirmed by echocardiography. After 1 day, correct placement of the ring results in an increased flow velocity in the transverse aorta over the o-ring-induced stenosis. After 2 weeks, impaired cardiac function is proven by decreased ejection fraction and increased wall thickness. Importantly, besides less variance in the diameter size, ORAB is associated with lower intra- and post-operative mortality rates compared with transverse aortic constriction (TAC). Thus, ORAB represents a superior method to the commonly used TAC surgery, resulting in more reproducible results and a possible reduction in the number of animals needed.